Circulating Plasma Biomarkers in Biopsy-Confirmed Kidney Disease. Issue 1 (January 2022) - Schmidt, Insa M.; Sarvode Mothi, Suraj; Wilson, Parker C.; Palsson, Ragnar; Srivastava, Anand; Onul, Ingrid F.; Kibbelaar, Zoe A.; Zhuo, Min; Amodu, Afolarin; Stillman, Isaac E.; Rennke, Helmut G.; Humphreys, Benjamin D.; et al.
Visual Abstract: Abstract : Background and objectives: Biomarkers for noninvasive assessment of histopathology and prognosis are needed in patients with kidney disease. Design, setting, participants, & measurements: Using a proteomics assay, we measured a multimarker panel of 225 circulating plasma proteins in a prospective cohort study of 549 individuals with biopsy-confirmed kidney diseases and semiquantitative assessment of histopathology. We tested the associations of each biomarker with histopathologic lesions and the risks of kidney disease progression (defined as ≥40% decline in eGFR or initiation of KRT) and death. Results: After multivariable adjustment and correction for multiple testing, 46 different proteins were associated with histopathologic lesions. The top-performing markers positively associated with acute tubular injury and interstitial fibrosis/tubular atrophy were kidney injury molecule-1 (KIM-1) and V-set and Ig domain-containing protein 2 (VSIG2), respectively. Thirty proteins were significantly associated with kidney disease progression, and 35 were significantly associated with death. The top-performing markers for kidney disease progression were placental growth factor (hazard ratio per doubling, 5.4; 95% confidence interval, 3.4 to 8.7) and BMP and activin membrane-bound inhibitor (hazard ratio, 3.0; 95% confidence interval, 2.1 to 4.2); the top-performing markers for death were TNF-related apoptosis-inducing ligand receptor-2 (hazard ratio, 2.9; 95% confidence interval, 2.0 to 4.0) and CUB domain-containing protein-1 (hazard ratio, 2.4; 95% confidence interval, 1.8 to 3.3). Conclusion: We identified several plasma protein biomarkers associated with kidney disease histopathology and adverse clinical outcomes in individuals with a diverse set of kidney diseases. Podcast: This article contains a podcast at https://www.asn-online.org/media/podcast/CJASN/2021_12_28_CJN09380721.mp3